Principles of Investment Activity (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article examines the methodological significance of the categories “concept” and “principles” in relation to organizing the process of investing in the real sector of the economy. The author systematizes the content and evolution of the views of representatives of various economic schools on the process of investing in the real sector of the economy in conceptual and fundamental aspects. Due to the debatable nature of the problem under consideration, the author’s interpretation of the categories “concept” and “principle” in relation to the investment process is substantiated.